2002
DOI: 10.7547/87507315-92-8-444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Plantar Fascia Bands

Abstract: The authors measured the thickness of the medial, central, and lateral bands of the plantar fascia using ultrasonographic techniques in 109 symptomatic patients with 211 painful heels. Plantar fasciitis was diagnosed by the presence of plantar heel pain and tenderness of the plantar fascia on palpation and was correlated with plantar fascia thickness. All of the symptomatic feet had medial band tenderness, with an average thickness of 5.9 mm, 68% had central band tenderness, with an average thickness of 5.3 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, two studies could not be included: one study [31] reported data separately for the medial, central and lateral components of the plantar fascia, and another study [30] did not report the standard deviation of the mean plantar fascia thickness values.…”
Section: Resultsmentioning
confidence: 99%
“…However, two studies could not be included: one study [31] reported data separately for the medial, central and lateral components of the plantar fascia, and another study [30] did not report the standard deviation of the mean plantar fascia thickness values.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 4) [16, 4757]. Hyperaemia is a well-known feature of tendinopathy due to neurovascular growth and may contribute to pain.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Therefore, it is essential that podiatry management strategies for plantar fasciitis are underpinned by EBP principles to ensure that optimal outcomes are attained. Although most commonly described as an inflammatory condition (plantar fasci’ itis ), researchers have questioned the presence of inflammation in this condition 4,5. Plantar fasciitis is reported to commonly occur in runners and those who are overweight 69.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this limited evidence base, in clinical practice, CFO and CSI remain popular, possibly driven by patient expectations and fee for service model. Confounding these issues are the known side effects, discomfort, and injection pain respectively for the use of CFO and CSI 4,5,23–26…”
Section: Introductionmentioning
confidence: 99%